Large Duodenal Adenoma Causing Significant Bleeding Successfully Removed by Endoscopic Measure- Case Report (Pulse, 2026)
BACKGROUND: Brunner’s gland adenoma is a rare benign tumor arising from the submucosal glands of the duodenum. Most lesions are small and asymptomatic, but larger tumors may present with gastrointestinal bleeding, anemia, or obstruction. Lesions located in the distal duodenum may be difficult to detect with conventional endoscopyCASE PRESENTATION: A 67-year-old man with hypertension and diabetes presented with recurrent melena for two years, worsening over the previous two months. Prior evaluations, including esophagogastroduodenoscopy, side-viewing endoscopy, and colonoscopy, failed to identify the bleeding source. He was found to have severe iron deficiency anemia (hemoglobin 7.2 g/dL). Contrast-enhanced CT revealed an intraluminal lesion in the third part of the duodenum. Further evaluation using a pediatric colonoscope enabled deeper duodenal intubation and identified a large bleeding pedunculated polyp in the second part of the duodenum. Endoscopic treatment with adrenaline injection, hemoclip placement, and snare polypectomy was successfully performed. The resected polyp measured 5.5 cm, and histopathology confirmed Brunner’s gland adenoma. The patient recovered uneventfully with resolution of bleeding and improvement in hemoglobin levels.CONCLUSION: Brunner’s gland adenoma should be considered in patients with unexplained recurrent upper gastrointestinal bleeding and iron deficiency anemia when routine endoscopy is inconclusive. Advanced endoscopic techniques allowing deeper duodenal examination can facilitate diagnosis, and endoscopic resection provides effective definitive treatment.Pulse Volume 17, Issue 2 2025; 41-44